Laboratory Study of Geotechnical Characteristics of Soil in Landslide-Prone Zone in Talamau District, West Pasaman Regency - Nofrizal; Fauzan; Abdul Hakam; Bambang Istijono; Andriani Setiawan; Aprisal (Postgraduate, University of Mataram, 2025)
The main triggering factor for landslides is high rainfall intensity, especially during the rainy season. Excessive rainfall can cause an increase in water content in the soil, which in turn will reduce the shear strength of the soil and increase the volume weight of the soil. The method used is a laboratory experiment by taking samples from the field. The sample of this study was sandy clay soil taken from a landslide-prone area located in Talamau District, West Pasaman Regency. Based on the results of soil geotechnical laboratory tests in the landslide-prone zone in Talamau District, West Pasaman Regency, it can be concluded that the soil sample has moderate plasticity characteristics with a Liquid Limit of 59.39%, Plastic Limit of 49.77%, and Plasticity Index of 9.62%. The soil reaches a maximum dry density of 1.37 gr/cm³ at an optimum water content of 500 ml, with a grain size distribution dominated by the sand fraction (83.978% retained on sieve No. 4-20) and a very low fine material content (1.234%). The results of the triaxial test showed soil behavior that varied from brittle to strain-hardening depending on the level of cell stress. Overall, the soil can be classified as well-graded sand with good drainage but low cohesion, thus requiring additional stabilization for construction applications in landslide-prone areas.